ADAM23 is a negative regulator of Kv1.1/Kv1.4 potassium currents. (21st June 2019) - Lancaster, Eunjoo; Burnor, Elisabeth; Zhang, Junxian; Lancaster, Eric
Highlights: ADAM23 is a negative regulator of Kv1.1 potassium currents. ADAM22 in the presence of LGI1 positively regulates Kv 1.1 currents. The regulation of Kv 1.1 by LGI1 and the ADAM proteins may contribute to neuronal hyperexcitability in diseases with loss of LGI1. Abstract: Background ADAM22 and ADAM23 are transmembrane proteins that bind the secreted synaptic protein LGI1 and associate with Kv 1.1/Kv 1.4 potassium channels. However, the roles of these proteins in regulated voltage-gated potassium currents are poorly understood. Methods Cultured cells were transfected to express ADAM22, ADAM23, and Kv 1.1/Kv 1.4. Voltage-gated potassium currents were measured by whole-cell patch-clamp. Immunostaining Kv 1.1 with fluorescent antibodies and fluorescently tagged Kv 1.1 subunits was used to measure the effects of ADAM proteins on cell-surface and total expression of Kv 1.1 channels. LGI1-conditioned media was added to assess the effect on LGI1 on Kv 1.1 currents. Results Cells transfected with Kv 1.1/Kv 1.4 showed voltage-gated potassium currents (Kv1.1 currents). ADAM23 was a powerful negative regulator of Kv 1.1 currents and caused decreased surface expression of Kv 1.1 subunits. This decrease in current was not mediated by clathrin-dependent endocytosis. LGI1-conditioned media did not affect the negative regulation of Kv 1.1 currents by ADAM23. ADAM22 had no significant effect on Kv 1.1 currents by itself, but in the presence of LGI1-conditioned media markedly potentiated Kv 1.1 currents without changing channel activation kinetics. Conclusions ADAM22 and ADAM23 have opposite effects on Kv 1.1 currents. The relative expression of these proteins, and the availability of LGI1 may shape the expression of Kv 1.1 currents in different neuronal membrane domains.